Vitamin K3 and vitamin C alone or in combination induced apoptosis in leukemia cells by a similar oxidative stress signalling mechanism (2011)
ABSTRACT: Background: Secondary therapy-related acute lymphoblastic leukemia might emerge following chemotherapy and/or radiotherapy for primary malignancies. Therefore, other alternatives should be pursued to treat leukemia. Results: It is shown that vitamin K3- or vitamin C- induced apoptosis in leukemia cells by oxidative stress mechanism involving superoxide anion radical and hydrogen peroxide generation, activation of NF- B, p53, c-Jun, protease caspase-3 activation and mitochondria depolarization leading to nuclei fragmentation. Cell death was more prominent when Jurkat and K562 cells are exposed to VC and VK3 in a ratio 1000:1 (10 mM: 10 μM) or 100:1 (300 μM: 3 μM), respectively. Conclusion: We provide for the first time in vitro evidence supporting a causative role for oxidative stress in VK3- and VC-induced apoptosis in Jurkat and K562 cells in a domino-like mechanism. Altogether these data suggest that VK3 and VC should be useful in the treatment of leukemia.